MICROSEISMIC ACTIVITY IN THE HELLENIC VOLCANIC ARC, GREECE, WITH EMPHASIS ON THE SEISMOTECTONIC SETTING OF THE SANTORINI-AMORGOS ZONE - Bohnhoff M.; Rische M.; Meier T.; Becker D.; Harjes H.-P.; Stavrakakis G. (My University, 2006)
The volcanic arc of the Hellenic subduction zone with its four volcanic centers is of major relevance when evaluating the seismovolcanic hazard for the Aegean region. We present results from a 22-station temporary seismic network (CYCNET) in the central Hellenic Volcanic Arc (HVA). CYCNET recordings allow to analyze the level and spatio-temporal evolution of microseismic activity in this region for the first time. A total of 2175 events recorded between September 2002 and July 2004 are analyzed using statistical methods, cluster analysis and relative relocation techniques. We identify distinct regions with significantly varying spatio-temporal behavior of microseismicity. A large portion of the seismic activity within the upper crust is associated with the presence of islands representing horst structures that were generated during the major Oligocene extensional phase. In contrast, the central part of the Cyclades metamorphic core complex remains aseismic considering our magnitude threshold of 1.8 except one spot where events occur swarm-like and with highly similar waveforms. The highest activity in the study area was identified along the SW-NE striking Santorini-Amorgos zone. Within this zone the submarine Columbo volcano exhibits strong temporal variations of seismic activity on a high background level. This activity is interpreted to be directly linked to the magma reservoir and therein the migration of magma and fluids towards the surface. NE of Columbo where no volcanic activity has yet been reported we observe a similar seismicity pattern with small-scaled activity spots that might represent local pathways of upward migrating fluids or even developing volcanic activity within this zone of crustal weakness. In contrast, the Santorini and Milos volcanic complexes do not show significant temporal variations and low to moderate background activity, respectively. Relating our results to the distribution of historical earthquakes and the GPS-derived horizontal velocity field we conclude that the Santorini-Amorgos zone is presently in the state of right-lateral transtension reflecting a major structural boundary of the volcanic arc subdividing it into a seismically and volcanically quiet western and an active eastern part. © 2006 Elsevier B.V. All rights reserved.
Keywords: HELLENIC SUBDUCTION ZONE; HELLENIC VOLCANIC ARC; SEISMOLOGY; SEISMOTECTONIC; TEMPORARY NETWORKS; Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен